2002
DOI: 10.2174/1389203023380413
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Detection and Localization of the Drug Transporter P-Glycoprotein in Cultured Tumor Cells

Abstract: In vitro studies on the cellular location of P-glycoprotein (Pgp) are reported with the aim to clarify the relationship between its intracellular expression and the multidrug resistance (MDR) level of tumor cells. Pgp was found abnormally expressed on the plasma membrane of tumor cells with "classical" MDR phenotype. However, Pgp was also often detected on the nuclear envelope and on the membrane of cytoplasmic organelles. The hypothesis that this drug pump maintains a transport function when located in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 0 publications
3
60
0
Order By: Relevance
“…Recently, the ATP-binding cassette transporter family member proteins that are strongly connected to the drug resistance phenotype, such as P-glycoprotein, MRP1, and BCRP, have been localized to intracellular membranes. Such findings further highlight the relevance and importance of the sequestration mechanism in drug resistance (25,26).…”
Section: Introductionmentioning
confidence: 61%
“…Recently, the ATP-binding cassette transporter family member proteins that are strongly connected to the drug resistance phenotype, such as P-glycoprotein, MRP1, and BCRP, have been localized to intracellular membranes. Such findings further highlight the relevance and importance of the sequestration mechanism in drug resistance (25,26).…”
Section: Introductionmentioning
confidence: 61%
“…Nevertheless, some studies have demonstrated its localization in intracellular sites such as the nuclear envelope and in the membrane of cytoplasmatic organelles (11). These studies suggest that Pgp function is related to cellular protection against toxic agents, independently of its localization.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of P-gp have mainly focused on the expression of plasma membrane P-gp. However, recent studies have shown that P-gp expression is observed at the intracellular membranes in tumor-resistant cells, including the nucleus, Golgi apparatus, and the some unconfirmed cytoplasmic vesicles such as lysosomes and inclusion bodies (2)(3)(4). Furthermore, intracellular levels of P-gp are roughly equivalent to that of the plasma membrane P-gp.…”
Section: Introductionmentioning
confidence: 99%